Balanço geoquímico e pedogênese sobre rochas cristalinas ácidas na região do Caparaó, Espírito Santo - Loureiro, Ramon Machado (2022)
Over time, several studies have been carried out with the aim of understanding in depth the factors and processes of soil formation in the world. The understanding of the geochemical and mineralogical balance, allied to the indices of weathering, has promoted conditions to estimate future stages of soils, element mobility, leaching processes and agricultural potential. Thus, the objective of this work was to understand the geochemical dynamics and pedogenic processes in colluvium ramp on acid crystalline rock in the region of Caparaó, Espírito Santo. Four profiles were collected along the slope; the horizon samples were air-dried, crushed and passed through a 2 mm mesh sieve, obtaining air-dried fine earth (TFSA). Soil characterization and geochemical balance determination was based on routine chemical and physical analysis, x-ray fluorescence (XRF). The mineralogical composition of clay minerals was analyzed by X-ray diffractometry (XRD), magnetic susceptibility analysis, selective extractions of iron forms and thermogravimetric curves (TG). Based on the data obtained, it can be concluded that: a) the relief had a strong influence on pedogenesis due to its contribution to the distribution, infiltration and dynamics of water in the system, as well as to the continuous contribution of colluvial detritus, which exerts a rejuvenating effect in soils, especially in surface horizons; b) through the weathering indices, the soils were classified in an intermediate stage of weathering, close to complete kaolinization, indicating a degree of pedogenic evolution of the profiles in the order P4>P1>P2>P3; c) the mineralogical assembly of the clay fraction is dominated by kaolinite and illite, crystalline Fe oxyhydroxides (hematite and goethite), gibbsite and K-feldspar, in a smaller proportion are found plagioclases and vermiculite with hydroxy-Al interlayers; d) the high activity of the clay fraction on the surface, especially in P1 and P2, evidences the significant participation of illite in the cation exchange capacity of soils, possibly due to the partial removal of K in the interlayers (mineral interstratification), resulting in a small expansion capacity and contraction of the 2:1 layers, and consequent increase in cation exchange capacity and specific surface; e) the inverse kaolinite-gibbsite relationship does not reflect the pedogenic stage of the soils, confirmed by the higher levels of gibbsite at depth in the saprolite (P2-Cr).